Variation in the Essential Oil Content and its Composition in Eucalyptus cinerea Leaves and its Relation to Some Environmental Factors. Issue 4 (4th July 2017) - Heikal, Amaal Abd-Elkhalek Mohamed
Abstract: Changes in temperatures, relative humidity and day length play an important role in the variation of essential oils contents and its compositions in medicinal and aromatic plants. In order to investigate the influence of seasonal variations on essential oil and its compositions, leaves of Eucalyptus cinerea harvested bimonthly (from July 2015 to May 2016). Essential oil was extracted from fresh and dried leaves by water distillation and its composition was determined by GC-MS analysis. Variation in temperatures, relative humidity and day length throughout different months markedly affected the quantity and quality of essential oil. Dry leaves yielded significantly higher essential oil than the corresponding samples of fresh leaves throughout all harvesting dates. The highest essential oil content was found in fresh (1.94%) and dried (3.19%) leaves harvested in September, while the lowest content of essential oil was found in fresh (0.98%) and dried (1.75%) leaves harvested in January. 1, 8-cineole was the major constituent of essential oil in fresh (44.56 - 74.26%) and dried leaves (51.98 - 81.29%). The highest content of 1, 8-cineole was determined in essential oil of leaves harvested in September. Essential oil and 1, 8-cineole contents had positive and significant correlations with N and K leaves contents, while they had a negative and significant correlations with reducing sugar content in the leaves. Step-wise regression analysis showed that maximum, minimum and average temperatures as well as day length designated as the important environmental factors to explain variations of fresh and dry leaves essential oil contents.